A case of maternal–foetal chimerism identified during routine histocompatibility testing for hematopoietic stem cell transplantation. (12th December 2015) - Grubic, Z.; Stingl Jankovic, K.; Kelecic, J.; Batinic, D.; Dubravcic, K.; Zunec, R.
Summary: This report describes a case of maternal‐foetal chimerism identified in a boy diagnosed with SCID, who underwent HLA testing in preparation for HSCT. The first analysis was carried out on DNA from peripheral blood and included HLA‐A, HLA‐B, HLA‐DRB1 typing using PCR‐SSO. The patient's HLA‐B typing results were noninterpretable. All samples were re‐typed for HLA‐B using PCR‐SSP, again resulting in noninterpretable typing of patient's HLA‐B. In both cases, several weak positive probes/reactions interfered with the interpretation when using commercial software. Next round of HLA typing, using PCR‐SSP and PCR‐SSO methods, included the patient's bone marrow sample and HLA‐C locus, but interpretation was again not possible. The PCR‐STR analysis performed on both peripheral blood and bone marrow samples revealed seven STRs for which two maternal and one paternal allele were detected. Retrospective manual interpretation of HLA‐B and HLA‐C typing revealed that weak positive reactions were indeed owed to paternal HLA‐B and HLA‐C alleles and that the patient had both maternal and one paternal allele. Retyping of HLA‐B and HLA‐C loci and STR analysis on the patient's buccal cells sample revealed the expected one maternal/one paternal allele pattern. In summary, the combination of several different typing methods and manual interpretation were necessary to obtain the patient's HLA typing results.